2020
DOI: 10.3390/ph13060119
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Selective Estrogen Therapy Prevents Androgen Deprivation-Associated Hot Flushes in a Rat Model

Abstract: Hot flushes are best-known for affecting menopausal women, but men who undergo life-saving castration due to androgen-sensitive prostate cancer also suffer from these vasomotor symptoms. Estrogen deficiency in these patients is a direct consequence of androgen deprivation, because estrogens (notably 17β-estradiol, E2) are produced from testosterone. Although estrogens alleviate hot flushes in these patients, they also cause adverse systemic side effects. Because only estrogens can provide mitigation of hot flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…Therefore, confining E2 into the brain also is critical for these patients. Using orchiectomized rats in the same model of morphine-dependent hot flushes as for the female animals, we have also shown the beneficial TST lowering effect of the DHED-derived E2 ( Figure 3 ) in male animals lacking gonadal E2 source ( 108 ).…”
Section: E2 and Vms (Hot Flushes)mentioning
confidence: 57%
“…Therefore, confining E2 into the brain also is critical for these patients. Using orchiectomized rats in the same model of morphine-dependent hot flushes as for the female animals, we have also shown the beneficial TST lowering effect of the DHED-derived E2 ( Figure 3 ) in male animals lacking gonadal E2 source ( 108 ).…”
Section: E2 and Vms (Hot Flushes)mentioning
confidence: 57%
“…Through an extensive series of supporting and multidisciplinary experiments as well as validated bioanalytical assays (e.g., Prokai et al, 2003Prokai et al, , 2015Prokai-Tatrai et al, 2018, 2021Merchenthaler et al, 2016Merchenthaler et al, , 2020, metabolism of these steroidal para-quinol bioprecursor prodrugs (HEDD, DHED and αDHED) to the corresponding estrogen (E1, E2 and 17-estradiol [E2], respectively) has been unequivocally demonstrated to occur in the CNS (Figure 1A) without peripheral hormonal effects. Specifically, these experiments explicitly revealed that estrogen-sensitive organs such as the uterus, seminal vesicle and anterior pituitary were not stimulated by HEDD, DHED or αDHED treatments, even after chronic dosing.…”
Section: Resultsmentioning
confidence: 99%
“…As reported in Table 5, quinols 3a and 3c-d were obtained ranging from acceptable to high yield (Table 5, entry 1 and entries 3-4). Quinols 3a (DHED) and 3c (HEDD) are well recognized pro-drugs in Hormone Replacement Therapy [9][10][11][12][13][14]. The reaction was performed solubilizing 1b (0.2 mmol) and meso-TPP (1.0 mol%) in 2-MeTHF (3.2 mL), followed by the addition of PBS (0.1 M, pH 6) and of PPh3 (0.3 mmol) at different reaction times.…”
Section: Entrymentioning
confidence: 99%
“…As reported in Table 5, quinols 3a and 3c-d were obtained ranging from acceptable to high yield (Table 5, entry 1 and entries 3-4). Quinols 3a (DHED) and 3c (HEDD) are well recognized pro-drugs in Hormone Replacement Therapy [9][10][11][12][13][14].…”
Section: Entrymentioning
confidence: 99%
See 1 more Smart Citation